Exogenously applied Casuarina equisetifolia leaf extracts act as an osmoprotectant on proline accumulation under drought stress in local rice from Indonesia - Salsinha, Yustina Carolina Febrianti; Rini, Dwi Setyo; Indradewa, Didik; Rachmawati, Diah; Alam, Taufan; Purwestri, Yekti Asih (Frontiers in Plant Science, 2023)
The effects of exogenously supplied osmoprotectants in crops have not yet been extensively studied. In this study, an osmoprotectant containing a high concentration of proline (2.5 g mol−1 FW) was obtained from a Casuarina equisetifolia leaf extract. The effect of the extract was evaluated in local Indonesian rice cultivars Boawae Seratus Malam (BSM), Gogo Jak (GJ), Situ Bagendit (SB) (drought-tolerant), Kisol Manggarai (KM) and Ciherang (drought-susceptible) cultivars under drought at the morphological, physiological, and genetic levels. Under drought, the KM showed an increased level of OsWRKY, OsNAC, OsDREB1A, and OsDREB2A expression after application of the osmoprotectant, leading to the activation of proline synthesis genes including OsP5CS1, OsP5CR, and OsProDH, while the tolerant cultivars (BSM, GJ, and SB) showed no difference. The content of chlorophyll, carotenoids, anthocyanins, ascorbate peroxidase, catalase, and superoxide dismutase activities also increased in GJ and KM, during drought stress and applied osmoprotectants, but remained low in the BSM. We conclude that the foliar application of osmoprotectants derived from C.equisetifolia caused an accumulation of proline in susceptible plants. The existence of these extracts stabilizes leaf cells and supports photosynthetic compartments and carbon assimilation in plants, leading to growth.